Turning Beats into Voices of Change: Moral Values in Papuan Urban Music - Sulistyowati, Ambar; Kreuta, Daniel (Grenek: Jurnal Seni Musik, 2024)
This study investigates the transformative role of urban music, particularly Hip-Hop, in addressing moral values within the Papuan context. Young Papuan musicians utilize Hip-Hop as a medium for social critique and cultural expression, embedding themes such as justice, environmental stewardship, and resilience in their lyrics. Employing a qualitative approach, the research analyzed song lyrics, performances, and social media content from members of the Bhuyaka Art Center, complemented by in-depth interviews. The findings reveal that Papuan Hip-Hop artists effectively navigate global influences while maintaining cultural authenticity, using music to critique systemic injustices and celebrate local heritage. Notably, the integration of local linguistic elements underscores its role in preserving cultural identity amidst globalization. The study highlights the genre's dual function as an expressive art form and a tool for advocacy, bridging local and global narratives. This research contributes to the discourse on urban music as a catalyst for cultural preservation and moral discourse, emphasizing its potential in fostering societal change and empowering marginalized communities